Religious ethics in industrialization process - Fatah Yasin, Raudlotul Firdaus; Zainan Nazri, Nurul Jannah; Jani, Mohd. Shah (American Research Institute for Policy Development, 2013)
The most important matter in ethics and values in industrialization process according to Islam is the matter of existence itself and how it is to be defined. Another issue is the matter concerning resources and how it is to be utilized. Therefore, this study deals with both basic issues by exploring the general guiding principles and values in the process of industrialization.